Szkoły prawnicze jako przykład „demokratyzacji” wymiaru sprawiedliwości w początkach Polski Ludowej - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper is devoted to the Ministry of Justice’s law schools. The author presents the origins of the institutions as well as the special nature of the decree of 1946 on exceptional admissions to the office of judge, prosecutor and notary, and entry into the list of barristers and solicitors under the Court System Law of 1928. He discusses the functioning of law schools and their curricula. He demonstrates that the introduction of a special system of appointments to various offices in the justice system in the early days of the People’s Republic of Poland stemmed from a lack of trust on the part of the new authorities in prosecutors and judges of the Second Polish Republic. Consequently, using staff shortages caused by the war and occupation as an excuse, the government decided to try to gain decisive influence on the justice system by appointing graduates of the law schools as judges and prosecutors, in return expecting loyalty to the new political authorities
Keywords: law schools; judge; prosecutors; training; judiciary